Using omega 3 as an anti-aging treatment - Carlos Iván Zavala Naranjo (Medisur)
Aging in general, and skin aging in particular, is a deleterious and universal process. Skin aging can be divided into chronological aging and photoaging, the latter being activated through damage to human skin, attributable to repeated exposure to ultraviolet (UV) rays from sunlight. Fatty acids derived from fish oil (omega 3) have been considered to be associated with photoprotection of the skin. The objective of this work is to describe the effects of omega 3 as an anti-aging drug in the elderly population. A bibliographic review of articles published between January 2010 and June 2020, in Pubmed and Google Scholar, was carried out. The available literature shows the effect and benefit of these fatty acids in the aging process, which constitute clinical therapies at the dermatological level and in areas of plastic surgery. Its use has a positive effect on the aging process in different organs, through action against oxidative stress.